Infrastructure Needs in Colombia and Public Private Partnerships (2017)
Public-Private Partnerships have become a common tool for designing, building, financing, operating and maintaining public infrastructure projects. The analysis of the public sector, under a traditional public works scheme, is dedicated to the period of construction of the asset, leaving the costs of operation and maintenance aside and outside the planning process of the project in question. Colombia, is one of the few Latin American countries with a strong capacity to implement projects of Public-Private Partnerships according to the report presented by the World Bank "Private financing of public infrastructures through PPPs in Latin America and the Caribbean", published on May 9, 2017. It is highlighted that the country's economy also has an advantage in attracting foreign investors compared to those of smaller countries.